International Financial Integration and Economic Growth in Developing Countries - Chang, Le (2006)
Empirical literature is very much divided on whether financial integration has a positive impact on economic growth. Until now, empirical work has not yet found a robust and convincing evidence for the existence of such relationship. As some countries have enjoyed the benefits of financial liberalization after it has been put in place, others have not and/or have even experienced severe crises and recessions during the years after the liberalization. Some argue that financial integration can not have effects on growth by itself. It has to be complemented by the country apostrophe s quality of institutions. Moreover, a number of scholars have argued, that the reason behind this positive effect being hard to detect, is failure to account for the negative impact of financial crisis on growth. Very few empirical studies have controlled the effects of crisis. We investigate empirically the effects of financial integration on economic growth in 55 developing countries across the 1980-2004 period. We examine the existence of causal relationship between financial integration and economic growth by applying various econometric methodologies. Through these methodologies we control the country apostrophe s specific effects and endogeneity of financial integration on economic growth. We also categorize the countries into more financially integrated and less financially integrated, in order to capture the potential outlier effects. We further investigate if this relationship depends on the quality of institutions, initial economic condition and macroeconomic condition. This study approaches the issue of the impact of international financial integration on economic growth from a novel perspective which has not yet been widely researched. This approach takes into consideration the importance of effects of financial crisis. According to the majority of our empirical results, we did not find strong evidence supporting that financial integration could boost economic growth in developing countries, even when taking into account country discrimination based on level of financial integration. The same result was also shown when controlling certain institutional, initial economic and macroeconomic factors. These effects did not show obvious difference between the ones without crisis control and the ones with such control.